Corrosion and Oxidation Resistance Behaviors of Ta-Containing Low Alloying Zirconium - Kim, Il-Hyun; Jung, Yang-Il; Choi, Byoung-Kwon; Kim, Hyun-Gil; Jang, Jae-Il (Metals and materials international, 2021)
Zirconium alloys are widely used to fabricate nuclear fuel claddings, and thus is desirable to improve the resistance of such alloys to corrosion and structural instability. In this study, Ta was used as an alloying element to improve the corrosion and oxidation resistance of zirconium alloys. The model alloy (TaZL) contained 0.03 wt% Ta and other elements with a proportion of less than 1 wt% in total (0.1 wt% Nb, 0.4 wt% Fe, 0.2 wt% Cr) in a zirconium base. The corrosion test involving pressurized water at 360 °C and oxidation test involving steam at 1200 °C indicated that TaZL exhibited the lowest weight gains among those of compared conventional and advanced Zr alloys. The corrosion and oxidation resistances of TaZL were respectively improved by 4 and 1.5 times compared to the corresponding values of Zircaloy-4. The microstructures of the oxide formed on TaZL were columnar along the oxide growth direction and did not change from columnar to equiaxed, which resulted in the high resistance of the alloy to corrosion and oxidation. Graphic Abstract